EXPLORING THE VOICES OF BLIND STUDENTS IN LEARNING AT UNIVERSITY (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2021)
Blind students are being part of our academic society, yet there is still a lack of study on the voices of blind students in their academic journey at university in Indonesia context. By investigating their effort in keeping up with the teaching and learning process, exploring their difficulties encountered along their study and technology used to assist, this study tackled this void. This research employed a descriptive case study design and 6 students at a private university from various majors were recruited voluntarily The data were gained from observation, questionnaire, and interview. The result of the research showed that most of the participants (95%) consider that being blind is not the end of the world. Blind students are resilient; they can adjust themselves to the academic society and have positive self-confidence (90%), even though they sometimes found discrimination in public areas (5%). Their resilience skill leads them to be persistent in the teaching and learning process, and make use of Screen reader application as their learning assistant (100%). However, the difficulties encountered are in Statistics and Mathematics subject since many symbols cannot be read by a Screen reader. In sum, their resilience skill will be very useful for developing and empowering their insight in learning at University.